Soal Matematika Model Programme For International Student Assesment (PISA) Pada Pembelajaran Matematika Sekolah Menengah - Nopriyanti, Tika Dwi; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Aisyah, Nyimas (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
Abstrak Pisa (Programme For International Student Assessment) Is one of the things that is set as an indicator of current learning success. Many studies to discuss PISA have been carried out in Indonesia so that various literatures are needed. This research methodology uses a liberature review system (SLR) where as a library that contains studies, evaluations of all research related to PISA. This study retrieves data via Google with the PISA syntax, PISA Questions, PISA Mathematics whit a range of 2018-2022 taking 35 articles to be studied and analysed.